Impact of a Nosocomial COVID-19 Outbreak on a Non-COVID-19 Nephrology Ward during the First Wave of the Pandemic in Spain - María Milagro Montero; Carlota Hidalgo López; Inmaculada López Montesinos; Luisa Sorli; Cristina Barrufet Gonzalez; Judith Villar-García; Roberto Güerri-Fernández; Milagros Herranz; Marta Crespo; María Dolores Arenas Jiménez; Julio Pascual; Cristina González Juanes; et al. (MDPI AG, 2021)
Introduction: The aim of this study was to analyze a nosocomial coronavirus disease 2019 (COVID-19) outbreak that occurred on a polyvalent non-COVID-19 ward at a tertiary care university hospital in Spain during the first wave of the pandemic and to describe the containment measures taken. The outbreak affected healthcare workers (HCWs) and kidney disease patients including transplant patients and those requiring maintenance hemodialysis. Methods: The outbreak investigation and report were conducted in accordance with the Orion statement guidelines. Results: In this study, 15 cases of COVID-19 affecting 10 patients and 5 HCWs were identified on a ward with 31 beds and 43 HCWs. The patients had tested negative for severe acute respiratory syndrome coronavirus 2 infection on admission. One of the HCWs was identified as the probable index case. Five patients died (mortality rate, 50%). They were all elderly and had significant comorbidities. The infection control measures taken included the transfer of infected patients to COVID-19 isolation wards, implementation of universal preventive measures, weekly PCR testing of patients and HCWs linked to the ward, training of HCWs on infection control and prevention measures, and enhancement of cleaning and disinfection. The outbreak was contained in 2 weeks, and no new cases occurred. Conclusion: Nosocomial COVID-19 outbreaks can have high attack rates involving both patients and HCWs and carry a high risk of patient mortality. Hospitals need to implement effective infection prevention and control strategies to prevent nosocomial COVID-19 spread.